Penggunaan Media Poster Huruf untuk Meningkatkan Aspek Membaca Permulaan pada Anak Usia 5-6 Tahun di Dusun 1 Desa Sambinasi - Rada, Maria Anna Ghena; Ita , Efrida; Ngura , Elisabeth Tantiana (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to improve early reading skills in children aged 5-6 years using learning media, namely letter poster media. The purpose of learning to read early childhood is to make children interested in reading activities so that these activities become fun activities. If the child already has a love of reading, it will be easier to be guided so that reading is not a burden but a necessity. One aspect of teaching that plays an important role is reading, especially beginning reading. Beginning reading is in the early stages of the reading process or visual process. The research method used is a qualitative descriptive research method where the researcher will specifically describe the data in the form of facts that actually come from the implementation of learning that is applied in hamlet 1, Sambinasi village, consisting of 6 girls and 2 boys with a total of 8 children, learning systematics starting from the planning, implementation and evaluation of the learning carried out. The results of the use of letter poster learning media for children in Hamlet 1, Sambinasi Village, have increased the aspects of beginning reading.